Numerical Investigation Of Flow Characteristics Of An Oscillatory Flow Across A Thermoacoustic Stack - Mustaffa., Siti Hajar Adni (2019)
Thermoacoustic system uses green technology to convert heat into electrical power or vice versa. The technology is attractive but the lack of understanding about fluid dynamics behavior of flow inside the system leads to the challenging issue in improving the system’s performance. Therefore, fundamental study of fluid dynamics in the complex thermoacoustic flow condition is needed. In this study, fluid dynamics investigations of an oscillatory flow across internal structure of a thermoacoustic system were carried out. Two dimensional CFD models of flow across structure known as “stack” inside thermoacoustic systems were solved using ANSYS CFD. The models were solved using laminar, Transition SST and SST k-ω turbulence models. The investigation covered drive ratios from 0.3 percent to 3.0 percent which corresponded to Stokes Reynolds number of 59 to 1722. A new investigation of the effect of flow frequency was also reported. The frequencies of flow was set at 13.1 Hz and 23.1 Hz. The CFD models were validated using experimental results. An experimental standing wave rig was developed and velocity data was measured and then used to validate the CFD models. The results of the CFD model agreed with experimental data with the errors ranging between 0.36 to 7.69 percent. Due to the limitation of the experimental rig, cases with drive ratio lower than 0.8 percent and higher than 1.6 percent were verified using theoretical solution. A good match was found between the CFD results and theoretical solution especially at low Reynolds number. Deviation between CFD results and theoretical predictions at high Reynolds number was discussed. Results were discussed based on velocity profiles and vorticity contour of flow within and around the “stack”. At 13.1 Hz, turbulence was found to start at a Reynolds number as low as 163. The start of turbulence was delayed to a Reynolds number of 308 as the frequency was increased to 23.1 Hz. The investigation of vortex shedding flow phenomena revealed nine patterns of vortex shedding evolution for both flow frequencies. The vortex that sheds at the end of structure will come back into the channel of the structure as the flow reversed. As a result, the entry length for this oscillatory flow was found to be better predicted using the well-established entry length equation for turbulence one-dimensional flow condition even if the oscillatory flow was laminar. Comparison between the current study and published works regarding the ratio of the channel height to the boundary layer thickness (D/δv) was also presented to strengthen the validity of the results of current study. The comprehensive fluid dynamics analysis reported in this study are expected to be beneficial for system that works with oscillatory flow condition especially the thermoacoustic systems.